Multi-objective genetic algorithm based approach for optimizing fuzzy sequential patterns - Kaya, M; Alhajj, R (Ieee Computer Soc, 2004)
This paper introduces the optimized sequential pattern problem and presents a novel approach to find such patterns. All the methods described in the literature to optimize association rules employ a single objective measure, such as optimized confidence or optimized support. In this study, we propose a novel multi-objective Genetic Algorithm (GA) based optimization method for optimizing quantitative sequential patterns. The objective measures of are support, confidence and a parameter related to the total number of fuzzy sets in the sequence. Experimental results on a synthetic database demonstrate the effectiveness and applicability of the proposed method.
16th IEEE International Conference on Tools with Artificial Intelligence -- NOV 15-17, 2004 -- Boca Raton, FL